ANALISIS PENANAMAN NILAI KARAKTER DALAM PEMBELAJARAN IPS MATERI KEBERAGAMAN BUDAYA KELAS IV SD - Noverawati Syah Fitri; Ade Irma Damayanti; Rizky Dellentya; Hamim Mullah Wahyu Ramadhan; Sri Wilda Ningsih; Priyono Tri Febrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social Studies (IPS) learning in elementary schools plays a strategic role in strengthening character education, particularly through the topic of cultural diversity. However, various studies indicate that the implementation of IPS learning still tends to focus on cognitive aspects and is not optimal in internalizing students' character values. This study aims to analyze the instillation of character values, identify developing values, and examine the role of teachers in IPS learning on cultural diversity in fourth-grade elementary schools. The study used a literature review method with a descriptive qualitative approach to 30 relevant scientific sources obtained through Google Scholar and Publish or Perish, using specific selection criteria. Data analysis was conducted thematically through a process of reduction, categorization, and drawing conclusions. The results indicate that the instillation of character values ​​is carried out in an integrated manner through learning activities such as discussions, group work, and an experience-based approach. The dominant character values ​​include tolerance, social care, mutual cooperation, nationalism, discipline, and responsibility. Teachers act as facilitators, motivators, and role models in shaping students' character. However, the effectiveness of character value instillation is still influenced by limitations in learning methods and media. Therefore, learning innovations are needed that are more contextual and oriented towards students' real-life experiences.